2024
DOI: 10.1039/d3cs00763d
|View full text |Cite
|
Sign up to set email alerts
|

The emerging chemistry of self-electrified water interfaces

Fernando Galembeck,
Leandra P. Santos,
Thiago A. L. Burgo
et al.

Abstract: Every real material system on the Earth's surface is a mosaic of electric charges supporting unexpected chemical reactions and electricity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 230 publications
0
2
0
Order By: Relevance
“…When silicon comes into contact with water, a complex interplay occurs among the native oxide layer of the silicon surface, water molecules, and dissolved species. This interaction leads to the formation of hydration layers with oriented dipoles, accumulation of charged ions, and ultimately, the development of an electric double layer at the interface. , This electrified interface can, in turn, modulate the electrochemical potential of silicon and influence the intensity of its surface band bending …”
Section: Resultsmentioning
confidence: 99%
“…When silicon comes into contact with water, a complex interplay occurs among the native oxide layer of the silicon surface, water molecules, and dissolved species. This interaction leads to the formation of hydration layers with oriented dipoles, accumulation of charged ions, and ultimately, the development of an electric double layer at the interface. , This electrified interface can, in turn, modulate the electrochemical potential of silicon and influence the intensity of its surface band bending …”
Section: Resultsmentioning
confidence: 99%
“…As early as 1892, Lenard noticed the presence of charged droplets in waterfall splashes, a phenomenon later verified in thunderstorms and fog through advancements in detection technology . Increasingly, it has been recognized that contact electrification promotes the separation of opposite charges when two different phases touch one another. , Recent research by Wang and co-workers and Galembeck and co-workers , confirmed that collisions between droplets can lead to charge transfer. The electrification of droplets affects the specific adsorption of water at interfaces and dipole changes, thereby altering the physicochemical properties of microdroplets.…”
Section: Introductionmentioning
confidence: 98%